Occurrence of Mormolyca cleistogama (Maxillarinae, Orchidaceae) in São Paulo state, Brazil - Marcusso, Gabriel Mendes (2018)
Abstract Mormolyca cleistogama has its occurrence unknown in São Paulo state, although widely distributed in South America. In this study, based in field collection, we confirmed the occurrence of M. cleistogama in São Paulo state, Brazil. Morphological descriptions, color images and comparison with the closely related taxon, M. rufescens, are presented.